Cutaneous Disease as Sole Clinical Manifestation of Protothecosis in a Boxer Dog - Emmanouil I. Papadogiannakis; Emmanouil N. Velonakis; Gregory K. Spanakos; Alexander F. Koutinas (Case Reports in Veterinary Medicine)
Prototheca wickerhamii is ubiquitous, saprophytic achlorophyllous algae that cause opportunistic infections in the dog and cat and disseminated disease usually in immunocompromised animals. In this report an uncommon case of canine cutaneous protothecosis is presented. A 6-year-old female boxer was brought in with skin lesions that consisted of nodules and generalized footpad hyperkeratosis, depigmentation, and erosion. Cytology and histopathology showed pyogranulomatous inflammation along with organisms containing round sporangia with spherical sporangiospores. PCR and sequencing identified the causal organism as Prototheca wickerhamii. Therapy applied in this patient with either fluconazole alone or combination of amphotericin B and itraconazole proved effective only for footpad lesions but not for skin nodules. Systemic therapy seems to be ineffective for skin nodules, at least in chronic cases of canine cutaneous protothecosis. Although canine protothecosis usually presents with the disseminated form, cutaneous disease as sole clinical manifestation of the infection may also be witnessed.